Parental Monitoring and Risk Behavior in Middle Adolescents (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2021)
Friends played significant role due to middle adolescents tended to imitate behaviour of their friends including the risk behaviour. Parental monitoring could minimize the risk. However, the excessive unreasonable parental monitoring tended to increase risk behaviour of middle adolescents. Therefore, the purpose of this study was to know whether perceived parental monitoring had a significant relationship with risk behaviour among middle adolescents. This study used quantitative method with two measuring instruments in the form of a questionnaire, Parental Monitoring Questionnaire which consisted of 25 items to measure parental monitoring and Adolescence Risk Behaviour Questionnaire which consisted of 15 items to measure risk behaviour. The participants in this study were 105 male senior high school student age 15-17 years, who lived with both of their parents in Jakarta. Correlation test results showed that there was a significant relationship between perceived parental monitoring and substance use, premarital sex, and criminal behaviour among middle adolescents. Based on these results, the researcher presented some discussion materials and the suggestions that needed to be considered for further research.